Modulating Neuro-Immune-Induced Macrophage Polarization With Topiramate Attenuates Experimental Abdominal Aortic Aneurysm - Chen, Xing; Li, Yang; Xiao, Jie; Zhang, Hua; Yang, Chuanlei; Wei, Zhanjie; Chen, Weiqiang; Du, Xinling; Liu, Jinping (Frontiers in Pharmacology, 2020)
The development of abdominal aortic aneurysm (AAA) is attributed to psychological and physical factors. Topiramate, which is an agonist of the GABAA receptor, makes contributions to neuronal disease and is partially involved in immune regulation, may be effective upon abdominal aortic aneurysm progression. We used experimental abdominal aortic aneurysm models: Angiotensin II (Ang II)–induced ApoE−/− male mice (Ang II/APOE model) in our study. In the Ang II/APOE model, all mice (n=64) were divided into 4 groups: sham group (PBS treatment), control group (Ang II treatment), low-dose group (Ang II + low-dose topiramate, 3 mg/d per mouse), and high-dose group (Ang II + high-dose topiramate, 6mg/d per mouse). All treatments began on the day after surgery. Moreover, collected tissues and cultured cell were used for histology and biochemical examination. In vitro, the effects of topiramate on bone marrow-derived macrophage stimulated by LPS were investigated. Our data implied that topiramate treatment significantly promoted macrophages preservation and conversion of M1 to M2 macrophage phenotypes in vivo and vitro. Accordingly, pro-inflammatory activities mediated by the M1 macrophages were decreased and the repair process mediated by M2 macrophages was enhanced. The low-dose and high-dose groups had abdominal aortic aneurysm incidences of 50% and 37.5%, respectively, compared with 75% in the control group. Topiramate, a promising drug for the psychological disease, that target neuro-immune-induced macrophage polarization may attenuate experimental abdominal aortic aneurysm progression.